Water Services Management and Governance Lessons for a Sustainable Future - Katko, Tapio; Juuti, Petri (IWA Publishing, 2012)
This book focuses on water services, including water supply and wastewater services and deals with the connections between these. It covers water supply mainly in urban communities, sanitation and pollution control and water resources and their linkages to water services. This book is divided in to four key sections relating to governance frameworks, technology and socio-ecological interactions, government and governance, and long terms policies. The chapters analyse the complexity of the water services sector based on a historical analysis of developments within the sector. The underlying conviction is that only by understanding past trends, processes and developments can the current situation in the water services be understood. Only through this understanding can policies for sustainable water services in the future be formulated. The four key sections relate to governance frameworks, technology and socio-ecological interactions, government and governance, and long terms policies.